2007
DOI: 10.1177/0269215507082338
|View full text |Cite
|
Sign up to set email alerts
|

Tilted seat position for non-ambulant individuals with neurological and neuromuscular impairment: a systematic review

Abstract: Objective: To determine the effects of tilt-in-space seating on outcomes for people with neurological or neuromuscular impairment who cannot walk. Data sources: Search through electronic databases (MEDLINE, Embase, CINAHL, AMED). Discussions with researchers who are active in field. Review methods: Selection criteria included interventional studies that investigated the effects of seat tilt on outcome or observational studies that identified outcomes for those who had used tilt-in-space seating in populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
(89 reference statements)
0
21
0
Order By: Relevance
“…The posterior tilting position by 20 degrees in a tilt-in-space wheelchair can reduce load taken through the ischial tuberosities [25].…”
Section: Advantagesmentioning
confidence: 99%
“…The posterior tilting position by 20 degrees in a tilt-in-space wheelchair can reduce load taken through the ischial tuberosities [25].…”
Section: Advantagesmentioning
confidence: 99%
“…12 In the literature, there are several studies investigating the effect of wheelchair tilt-in-space and recline angles on seating interface pressure, but no research studies have been conducted to investigate the effect of the durations of tilt-in-space and recline on reducing soft tissue ischemia. 8, 11, 12 …”
mentioning
confidence: 99%
“…Although evidence regarding the use of wheelchair tilt-in-space and recline to reduce seating interface pressure exists,16, 18, 2123 the exact impact on skin blood flow and tissue viability is unclear 24, 25. Furthermore, inadequate pressure reduction by wheelchair tilt-in-space and recline may not benefit ischemic tissues 26.…”
mentioning
confidence: 99%
“…The guideline indicates that wheelchair tilt-in-space and recline should be recommended for wheelchair users at risk for pressure ulcers. The need to study the effectiveness of wheelchair tilt-in-space and recline was also indicated by a recent systemic review on the wheelchair tilt system 21. In order to understand the specific benefits associated with wheelchair tilt-in-space and recline, more research studies are needed to study the efficacy of various settings (angles, frequencies, and durations) of wheelchair tilt-in-space and recline on tissue viability.…”
mentioning
confidence: 99%